Adaptive control for a class of nonlinear time-delay systems with dead-zone input. Issue 17 (November 2016) - Zhang, Zhengqiang; Park, Ju H.; Zhang, Kemei; Lu, Junwei
Abstract: In this paper, we consider the same class of systems as in a previous paper, i.e. a class of uncertain nonlinear systems with state time-varying delays and nonsymmetric dead-zone input. The dead-zone parameters are unknown, and the delay-related nonlinearity is bounded by the partially known nonlinear functions. No knowledge is assumed on the slope sign of the dead-zone nonlinearity and the upper bounds of the time delays and their derivatives. By employing the Nussbaum gain approach and choosing a proper Lyapunov–Krasovskii functional, an adaptive compensation control algorithm is developed. The explicit expression of the control gain function is constructed. The boundedness of all the closed-loop signals is established, and the desired tracking performance is guaranteed by choosing the appropriate design parameters. The effectiveness of the proposed control algorithm is demonstrated by two simulation examples.